Addition of chemotherapy improves overall survival in patients with T2N0M0 non-small cell lung cancer undergoing definitive radiation therapy: An analysis of the SEER database. (February 2019) - Komiya, Takefumi; Chaaya, Gerard; Powell, Emily
Highlights: Chemotherapy improves survival in early stage patients undergoing radiation. Benefit of chemotherapy is largely seen in non-adenocarcinoma and primary tumors larger than 5 cm. Patients with primary tumors ≤5 cm may not benefit from chemotherapy. Abstract: Objectives: Despite recommendations by clinical guidelines, an advantage of adding systemic chemotherapy to definitive radiation in patients with early stage non-small cell lung cancer (NSCLC) has never been demonstrated by randomized or large-scale studies. This study evaluates the role of chemotherapy in T2N0M0 NSCLC patients who did not undergo surgical resection. Materials and methods: Using the Surveillance, Epidemiology, and End Results (SEER) database, we screened for patients with T2N0M0 NSCLC who received radiation therapy without surgical resection from 2004 to 2015. T-staging was defined according to the American Joint Committee on Cancer (AJCC) 6th (Year 2004+) and 7th (Year 2010+) versions. Overall survival based on chemotherapy status was assessed by univariate and multivariate analyses. Results: A total of 6075 and 3138 patients were identified for AJCC 6th (T2; 3–7cm) and 7th (T2a; 3–5 cm, T2b; 5–7 cm) version, respectively. Administration of chemotherapy was associated with younger age, male sex, non-adenocarcinoma, and high pathologic grade. Kaplan–Meier's estimates demonstrated that the chemotherapy group had a statistically significant longer five-year overall survival than the non-chemotherapy group in patients with AJCC 6th T2 (19.9% vs 15.8%, p  = 0.0023) and AJCC 7th T2b (5–7 cm, 20.9% vs 13.6%, p  = 0.0046) but not those with AJCC 7th T2a (3–5 cm, 24.3% vs 21.1%, p  = 0.4369). Multivariate analyses also revealed that the use of chemotherapy was an independent prognostic factor in AJCC 6th T2 and AJCC 7th T2b. Conclusions: This study strongly suggests that chemotherapy may benefit non-adenocarcinoma patients with primary tumor larger than 5 cm (AJCC 8th T3) undergoing chest radiation.